P917 Intestinal complement interacts with commensal microbiota and provides pattern recognition in Inflammatory Bowel Disease. (30th January 2023) - Reider, S; Posch, W; Koch, R; Orth-Höller, D; Würzner, R; Wilflingseder, D; Tilg, H; Moschen, A
Abstract: Background: The complement system is a central humoral part of innate immunity and provides essential pattern recognition capabilities as well as effector functions such as opsonisation and target cell lysis. Its prominent role in infection and immunity is undisputed but its involvement in the pathogenesis of inflammatory bowel diseases remains less clear. Published data point to a role of complement within the intestinal lumen supporting clearance of pathogens 1 . Methods: Expression of complement proteins within the intestinal epithelium was quantified by real-time qPCR on lesional and non-lesional biopsy samples from patients with IBD and healthy controls. The concentration of complement proteins was measured in fecal supernatants using ELISA. Flow cytometry of fecal bacterial single cell suspensions was used to assess complement (C3) and antibody (IgA) opsonisation status. Finally, cytometrically distinct populations were isolated by fluorescence-assisted cell sorting (FACS) and microbial community composition was investigated using 16S rDNA sequencing. Prediction of functional profiles from amplicon data was performed using Tax4Fun 2. Results: Complement expression in intestinal tissue was increased during active inflammation but certain targets were significantly less expressed in lesional mucosal sites (e.g. C6, C7). Free complement proteins in fecal supernatants were mostly undetectable by ELISA. In contrast, complement opsonisation was verified on fecal bacteria using flow cytometry. The degree of complement deposited on bacterial surfaces was significantly correlated with fecal calprotectin (p < 0.01). The percentage of complement-opsonized bacteria ranged from 0 to 5.3 % and did not correlate with intestinal inflammation while percentages of IgA opsonisation were generally higher (0.4 - 90.1%) and increased with fecal calprotectin (p < 0.01). FACS followed by 16S amplicon sequencing detected differences in bacterial taxa abundance between complement-opsonized, IgA-opsonized and non-opsonized fractions. Functional in-silico profiling revealed associations of complement-opsonization with bacterial virulence factors. Conclusion: Luminal and mucosal complement expression and activity is evident in patients with IBD. Complement opsonisation profiles are distinct from IgA opsonisation and show features of specificity regarding recognition of microbial features. References: 1 K.P. Aßhauer, B. Wemheuer, R. Daniel, P. Meinicke (2015) Tax4Fun: predicting functional profiles from metagenomic 16S rRNA data Bioinformatics (2015) 31 (17): 2882-2884. 2 Sorbara, M. T., et al. (2018). Complement C3 Drives Autophagy-Dependent Restriction of Cyto-invasive Bacteria. Cell Host Microbe 23(5): 644-652 e645.